Distribution of Chondrichthyans in the Greek Seas - Roxani Naasan Aga-Spyridopoulou; Kyriaki Pyloridou; Martina Ciprian; Ilektra Athinaiou; Stelios Katsanevakis; Dimitrios K. Moutopoulos; Ioannis Giovos (Fishes, 2026)
The Greek seas have hosted a diversity of sharks and rays since antiquity, with Aristotle providing the earliest detailed descriptions in his History of Animals, while the first modern documented record dates back to 1858. Despite this long history of attention and the acceleration of research on elasmobranchs over the past two decades, information on their spatial distribution remains fragmented, with most studies focusing on biological and fisheries-related parameters at low taxonomic and/or spatial resolution. This is concerning given that over 50% of Mediterranean chondrichthyans are now threatened with extinction. The present study reconstructs the distribution of extant species in the Greek seas by integrating published literature, mass and social media, biodiversity platforms, citizen science programs, research projects, and national datasets. Although records were compiled from 1858 onwards, only those starting from 1942 contained sufficiently precise locality information to be georeferenced. The review yielded 5596 spatial presence records of initially 67 species; however, after data validation, 62 species were confirmed: 33 shark species, 28 batoid species, and 1 chimaera species, of which 54.8% were from research programs, 30.5% were from published research, and 14.4% were from citizen science and were previously unpublished. These records enrich knowledge of threatened and data-deficient taxa and may serve as a useful baseline for future analyses and distribution modeling, as well as for informing marine spatial planning and conservation prioritization efforts in the eastern Mediterranean.

New insights in the distribution of the Smalltooth Sandtiger (Odontaspis ferox, Risso, 1810) in the Mediterranean - Kyriaki Pyloridou; Ilektra Athinaiou; Martina Ciprian; Roxani Naasan Aga-Spyridopoulou; Ioannis Giovos (Regional Studies in Marine Science, 2025)

Trace element levels in the sharks and rays of Amvrakikos Wetlands National Park, Greece - Ioannis Giovos; Martina Ciprian; Chiara Copat; Alberto Felici; George Katselis; Zoi Kazlari; Dimitrios Loukovitis; Carlotta Mazzoldi; Roxani Naasan Aga Spyridopoulou; Angie Sánchez-Rea; Francesco Tiralongo; Dimitrios K. Moutopoulos (Science of The Total Environment, 2025)

Marine Invasive Alien Species Reshape Small-Scale Fisheries: Case Study in Greek Coastal Waters - Dimitrios K. Moutopoulos; Nikoletta Sidiropoulou; Ioannis Vekris; Nikolaos Doumpas; Ioannis Giovos (Journal of Marine Science and Engineering, 2025)
The spread of non-indigenous species (NIS) in the Mediterranean poses complex challenges for coastal fisheries, yet the perceptions and adaptive responses of small-scale fishers remain poorly understood. This study surveyed 70 professional fishers across Greek insular and mainland ports to assess fishers’ local ecological knowledge, awareness, and operational strategies related to eleven established marine NIS. Semi-structured interviews recorded demographic and effort profiles, recognition rates, perceived environmental and economic impacts, catch frequencies, gear damage, injury incidents, and behavioral changes. Fishers in the study area demonstrated high overall awareness (~95%), but variable recognition of less familiar taxa (e.g., bigfin reef squid, squirrelfish). Venomous and gear-damaging species (pufferfish, lionfish, rabbitfish) were predominantly viewed negatively, with significant reported gear losses (EUR 600–1345 yr−1) and avoidance of high-incidence areas (25–30% of respondents). Conversely, commercially valuable NIS received more positive appraisals and are increasingly targeted. Spatial heterogeneity in perceptions and adaptations underscores the need for regionally tailored management that integrates fishers’ knowledge, promotes safe handling and selective exploitation of marketable NIS, and supports adaptive governance to mitigate ecological risks while enhancing socioeconomic resilience.

Assessing marine litter and its ecological impact on the seafloor of Thermaikos Gulf (NE Mediterranean Sea, Greece): Insights from ROV and diver surveys - Konstantina Kouvara; Evi Lazou-Laskaridis; Peggy Xirotagarou; Dimitris Christodoulou; Xenophon Dimas; Maria Geraga; Ioannis Giovos; Anastasia Charitou; Vasilis Gerovasileiou; Francois Galgani; George Papatheodorou (Marine Pollution Bulletin, 2025)

Distinct management units for the Critically Endangered angelshark (Squatina squatina) revealed in the Canary Islands - Eva K.M. Meyers; Nadia Faure; David Jiménez-Alvarado; Joanna Barker; Hector Toledo-Padilla; Fernando Tuya; Charlotte Pike; Lucy R. Mead; Michael J. Sealey; Maria Belén Caro; David M.P. Jacoby; Felipe Ravina Olivares; et al. (Conservation Genetics, 2025)
The angelshark, Squatina squatina , is listed as Critically Endangered on the IUCN Red List of Threatened Species, and remaining populations are highly fragmented throughout its historical distribution. The Canary Islands archipelago in the North East Atlantic has been identified as a uniquely large stronghold for the species. In the present study, we compared the population genetic structure of S. squatina across different islands of the Canary Island archipelago using both microsatellite and single nucleotide polymorphism (SNP) markers. Both markers revealed significant differentiation of angelsharks between islands in the archipelago, with three main genetic units at: (1) Tenerife, (2) Gran Canaria and (3) the island group consisting of La Graciosa, Lanzarote and Fuerteventura. Our results imply a connectivity barrier between some adjacent islands, most likely driven by abyssal depths, and varying geological history and formation of each island and oceanographic patterns (i.e. seasonal coastal upwellings off the African coast). Therefore, we suggest that in the Canary Islands, S. squatina populations should be managed locally, with conservation and research priorities designed and implemented specifically for each of the three genetic units.

Conservation and management of chondrichthyans in the Mediterranean Sea: gaps, overlaps, inconsistencies, and the way forward - Ioannis Giovos; Jennifer M. Pytka; Monica Barone; Lydia Koehler; Camille Loth; Jason Lowther; Dimitrios K. Moutopoulos; Simone Niedermüller; Carlotta Mazzoldi (Reviews in Fish Biology and Fisheries, 2024)
Over one third of sharks, rays and chimaeras (chondrichthyans) are threatened with extinction globally. In the Mediterranean Sea, more than half of chondrichthyan species face this risk, although a variety of international, regional, and national rules and regulations apply directly and indirectly targeting management and conservation for these species. In this work, we provide an overview of relevant legislation and policies in the region, which regulate, inter alia, commercial fisheries, while highlighting through cases studies how implementation in practice at national level looks like. Horizontal gaps and inconsistencies that hinder chondrichthyan management in the region are also illustrated. Furthermore, we present recommendations for improvement and additional tools that can be used, even if not originally or explicitly targeting chondrichthyans, for improving the management of these taxa in the Mediterranean.

Towards Cross-Border Fisheries Management: An Analysis of Fleet Structures and Species-Specific Regulatory Measures in the Aegean Sea - HAKKI DERELİ; VAHDET ÜNAL; AYLIN ULMAN; IOANNIS GIOVOS; ZAFER TOSUNOĞLU; GEORGE PRODROMITIS; DIMITRIOS K. MOUTOPOULOS (Mediterranean Marine Science, 2024)
Intrinsic differences in the applied management measures of shared stocks in transboundary waters inhibit the ability of either state to benefit from such measures, as one state may benefit in lieu of the other, thus reducing the efficacy of both. This study compares for the first time the fleet structure, specific management measures applied to species-specific regulations for commercial fishing, species listed in official monitoring schemes, and protected taxa between Greece and Türkiye for the Aegean Sea. A comparative analysis utilizing the official data was sourced from both countries. Large-scale Greek and Turkish fishing fleets have been modernized within the last 30 years (1991-2021). Greek and Turkish large-scale fishing fleets included smaller trawlers with lower tonnage and slightly higher engine horsepower, while purse seines of both states included larger vessels with higher horsepower and tonnage. This indicates that the fishing pressure on the demersal resources in the Aegean Sea has partially decreased, but the fishing pressure on pelagic resources has increased despite the decrease in the number of vessels. Only 11 out of 74 minimum conservation reference sizes (MCRS) are sufficiently set above the Lm50 sizes they should be based on, whereas 18 species need reproductive studies, and 22 are set below the Lm50, and could benefit from an increase. The application of specific closed seasons for commercial species was used by both states with the intent to protect the reproductive periods of some stocks. However, several of these closure periods did not fully or even partially cover the spawning periods of the respective species. Species-specific closures were applied to 13 species in Greece and 23 species in Türkiye, with only two fish species (Xiphias gladius and Thunnus thynnus) listed for both countries. Only 14 species (out of 34 protected by Greece and 46 by Türkiye) are protected by both states, most of which are listed as critically endangered by the International Union for Conservation of Nature and Natural Resources (IUCN). Harmonization of fisheries management measures currently does not align between the two neighbouring states, and the General Fisheries Commission of the Mediterranean is the competent authority that would be able to restructure such measures, especially as Türkiye has been aligning their measures with that of the EU for the accession process. This contribution highlights the clear differences between Greece and Türkiye, and provides advice for developing a unified management regime for the Aegean Sea.

Poor online information on European marine protected areas impairs public participation under the Aarhus Convention - Valentina Rossi; Carlo Pipitone; Katherine L. Yates; Fabio Badalamenti; Giovanni D’Anna; Cristina Pita; Fátima L. Alves; Jesús E. Argente-García; Jelena Basta; Joachim Claudet; Karsten Dahl; Simonetta Fraschetti; et al. (Marine Policy, 2024)

Elasmobranch Bycatch in a Bottom Trawl Fishery at Al Hoceima Port in Morocco (Mediterranean Sea) - Mohamed Keznine; Ioannis Giovos; Bilal Mghili; Sara A. A. AL-Mabruk; Mustapha Aksissou (Thalassas: An International Journal of Marine Sciences, 2024)

Engagement of fishers in citizen science enhances the knowledge on alien decapods in Cyprus (eastern Mediterranean Sea) - Christina Michail; Valentina Tanduo; Fabio Crocetta; Ioannis Giovos; Sofia Litsiou; Periklis Kleitou (Aquatic Ecology, 2024)

Assessing Consumer Attitude Towards Marine Non-Indigenous Fish Species: A Case Study From Greece (Eastern Mediterranean Sea) - Vasileios Minasidis; Nikolaos Doumpas; Ioannis Giovos; Periklis Kleitou; Alexandros Kaminas; Dimitrios K. Moutopoulos (Thalassas: An International Journal of Marine Sciences, 2023)
Non-indigenous fish species (NIFS) are spreading in the Mediterranean Sea, altering species assemblages and reshaping the marine ecosystems. Market-based approach has been promoted as a measure to limit the spread and damages by the NIFS and provide economic revenues to fishers. Understanding drivers of NIFS consumption and documenting consumers’ habits are pivotal in guiding a market strategy. Α custom-made online questionnaire was developed and distributed to Greek consumers through Social Media networks. The majority of consumers: (a) supported that NIFS are causing adverse effects to the marine environment (54%), (b) would consume NIFS products if they encountered them on a restaurant menu (62%), (c) would buy and consume NIFS provided they protect the marine environment and indigenous species (76%), and (d) hanker for the implementation of a quality control certificate on NIFS products (79%). Multivariate models revealed that the most important criteria for the consumers except for taste were the freshness of the products, whether the fish is poisonous, and the hygienic conditions of the fish market and its staff. The results reflected the positive attitude of the Greek consumers towards the consumption of NIFS and highlighted the importance of further promoting a market that could improve fisheries sustainability and challenge non-indigenous species (NIS) proliferation.

Assessing the current status of Hexanchus griseus in the Mediterranean Sea using local ecological knowledge - Ignasi Nuez; Ioannis Giovos; Francesco Tiralongo; Jaime Penadés-Suay; Ilija Cetkovic; Manfredi Di Lorenzo; Periklis Kleitou; Rigers Bakiu; Mohamed Nejmeddine Bradai; Sara A.A. Almabruk; Roxani Naasan Aga Spyridopoulou; Andréa Sabbio; et al. (Marine Policy, 2023)

Editorial: Biological invasions in the Mediterranean Sea - Francesco Tiralongo; Jason Michael Hall-Spencer; Ioannis Giovos; Periklis Kleitou (Frontiers in Marine Science, 2022)

An Updated Greek National Checklist of Chondrichthyans - Ioannis Giovos; Roxani Naasan Aga-Spyridopoulou; Fabrizio Serena; Alen Soldo; Adi Barash; Nikolaos Doumpas; Georgios A. Gkafas; Dimitra Katsada; George Katselis; Periklis Kleitou; Vasileios Minasidis; Yannis P. Papastamatiou; et al. (Fishes, 2022)
Accurate checklists of species are essential for evaluating their conservation status and for understanding more about their distribution, biology and ecology and, therefore, the first step in order to effectively protect them. According to the existing literature, the Greek seas are rich in chondrichthyan biodiversity and herein, we update the most recent chondrichthyan checklist for the country regarding the species that are present in the Greek waters, correct unvalidated miscellaneous sightings and observations and provide guidelines about future research to improve their conservation. In total, 330 sources were collected from which 276 were used for further analysis, resulting in 1485 records of 67 species, among which 61 are confirmed by experts, including 34 sharks, 26 batoids and one chimaera. We are further listing six species as “Questionable/Not Confirmed”.

Conflicting interests and growing importance of non‐indigenous species in commercial and recreational fisheries of the Mediterranean Sea - Periklis Kleitou; Dimitrios K. Moutopoulos; Ioannis Giovos; Demetris Kletou; Ioannis Savva; Leda L. Cai; Jason M. Hall‐Spencer; Anastasia Charitou; Maria Elia; George Katselis; Siân Rees (Fisheries Management and Ecology, 2022)
Non‐indigenous species (NIS) are spreading and reshaping Mediterranean Sea biological communities and fishery resources. The present study used fisheries data and structured interviews to assess the impacts of NIS on recreational and commercial fishers in Cyprus. NIS that have been present in Cyprus for more than two decades were mostly perceived by local fishers as native, NIS with high market value were considered to be beneficial, and venomous or poisonous NIS were considered to be deleterious. Pufferfishes (Tetraodontidae) were identified by fishers as causing significant economic damage, which undermines the sustainability of the commercial fishing sector. The most popular and highly priced NIS were rabbitfishes ( Siganus spp.). In terms of commercial landings, six non‐indigenous taxa contributed over a quarter of the total landing value and more than half during the summer season. The results of the present study emphasised the multifaceted interactions of NIS with the fishing sector, and how policy objectives may not align with social and commercial fishery interests.

Strengthening Angel Shark Conservation in the Northeastern Mediterranean Sea - Ioannis Giovos; Dimitra Katsada; Roxani Naasan Aga Spyridopoulou; Dimitrios Poursanidis; Aggeliki Doxa; Stelios Katsanevakis; Periklis Kleitou; Vasiliki Oikonomou; Vasileios Minasidis; Ayaka A. Ozturk; Dimitra Petza; Maria Sini; et al. (Journal of Marine Science and Engineering, 2022)
Angel sharks are among the most threatened species of sharks globally. Twenty-two species have been identified globally so far, with three species being present in the Mediterranean Sea: Squatina aculeata, Squatina oculata, and Squatina squatina. The Mediterranean populations of all three species have been assessed as Critically Endangered by the IUCN Red List of Threatened Species due to the steep decline of their populations as a result of their historical and current overexploitation by demersal fisheries. Therefore, currently there is an ongoing increasing effort for advancing the conservation of the species in the basin. Recently, in the context of the Regional Action Plan for Mediterranean Angel Sharks, the Aegean Sea and Crete have been identified as critical areas for all three species. This study provides the first predictive distribution map of the three angel shark species in the basin, while critical areas for the conservation of the species were identified through a systematic spatial conservation planning analysis. Our analysis revealed low overlapping between the existing MPA network and critical areas for the distribution of the species primarily in Greece and then Turkey, while 20% of the critical areas for the distribution of the species overlaps with Fisheries Restricted Areas of the region. This highlights the need for creating MPAs focusing on shark conservation within the Mediterranean that are currently completely absent. In addition, we provide policy recommendations that can secure better protection of angel sharks through the enforcement of the current legislations and the engagement of all relevant stakeholders.

Citizen Science Helps in Tracking the Range Expansions of Non-Indigenous and Neo-Native Species in Greece and Cyprus (Eastern Mediterranean Sea) - Joachim Langeneck; Vasileios Minasidis; Nikolaos Doumpas; Ioannis Giovos; Alexandros Kaminas; Periklis Kleitou; Francesco Tiralongo; Fabio Crocetta (Journal of Marine Science and Engineering, 2022)
Raising knowledge of the dispersal of non-indigenous species (NIS) in new geographic areas is a matter of major concern, as alien species may outcompete the native biota through competition, predation, and hybridization. In the Mediterranean Sea, where biological invasions constitute a serious threat, the combined use of citizen science and social networks amplified the results obtained via traditional research activities, often recording species that would otherwise presumably have passed unnoticed. We hereby report unpublished data for five NIS (the annelid Branchiomma luctuosum, the shrimp Saron marmoratus and the fishes Lutjanus argentimaculatus, Oxyurichthys petersii, and specimens of the group of Abudefduf saxatilis/vaigiensis/troschelii) and one neo-native species (Seriola fasciata) in Greece and Cyprus (eastern Mediterranean Sea), the majority of which were obtained via a focused citizen-science project and constitute new records at a country level. We also revise and update their known distribution in the invaded area, thus contributing to the study of large-scale and well-defined distributional patterns of alien species spreading in the Mediterranean Sea.

The use of fishers’ Local Ecological Knowledge to reconstruct fish behavioural traits and fishers’ perception of conservation relevance of elasmobranchs in the Mediterranean Sea - MATTEO BARBATO; CLAUDIO BARRÍA; ANDREA BELLODI; SARA BONANOMI; DIEGO BORME; ILIJA ĆETKOVIĆ; FRANCESCO COLLOCA; ANA I. COLMENERO; FABIO CROCETTA; FRANCESCO De CARLO; EGEMEN DEMİR; MANFREDI Di LORENZO; et al. (Mediterranean Marine Science, 2021)
The Mediterranean Sea has a long-lasting history of fishery exploitation that, together with other anthropogenic impacts, has led to declines in several marine organisms. In particular, elasmobranch populations have been severely impacted, with drastic decreases in abundance and species diversity. Based on their experience, fishers can provide information on marine species occurrence, abundance and behavioural traits on a long-term scale, therefore contributing to research on the poorly studied biological aspects of elusive or rare elasmobranch species. In this study, for the first time, the use of the Local Ecological Knowledge (LEK) of fishers was applied to study the behavioural traits of sharks, rays and skates in 12 FAO-GFCM geographical sub-areas (GSAs) of the Mediterranean Sea. This study found both new insight and proved the reliability of LEK-based catch seasonality, reflecting seasonal movements, by comparing LEK-based findings and available literature on five elasmobranch taxa (Mustelus spp., Squalus acanthias, Raja spp., Myliobatis aquila and Scyliorhinus stellaris) in the Adriatic Sea and 7 taxa (Mustelus spp., Raja spp., Prionace glauca, Scyliorhinus canicula, Torpedo spp., Pteroplatytrygon violacea and Isurus oxyrinchus) in the remaining Mediterranean GSAs. In addition, LEK provided new insights into a novel comprehensive representation of species aggregations (Mustelus spp., S. acanthias, M. aquila and S. canicula) in the sampled GSAs and supplied the first descriptions of the size, number of individuals and sex composition of the aggregations. When the limits and shortcomings of LEK-based research are considered, this methodology can be a complementary and cost-effective tool used to study elasmobranchs in either a data-poor scenario or a scenario in which a baseline is missing. LEK can also be useful for the evaluation and inclusion of fishers’ perceptions on bottom-up management and to provide important evidence for conservation plans.

Integrating Literature, Biodiversity Databases, and Citizen-Science to Reconstruct the Checklist of Chondrichthyans in Cyprus (Eastern Mediterranean Sea) - Ioannis Giovos; Fabrizio Serena; Dimitra Katsada; Athanasios Anastasiadis; Adi Barash; Charis Charilaou; Jason M. Hall-Spencer; Fabio Crocetta; Alexander Kaminas; Demetris Kletou; Mary Maximiadi; Vasileios Minasidis; et al. (Fishes, 2021)
Chondrichthyans are apex predators influencing the trophic web through a top-down process thus their depletion will affect the remaining biota. Notwithstanding that, research on chondrichthyans is sparse or data-limited in several biogeographic areas worldwide, including the Levantine Sea. We revise and update the knowledge of chondrichthyans in Cyprus based on a bibliographic review that gains information retrieved from peer-reviewed and grey literature, Global Biodiversity Information Facility (135 records of at least 18 species) and the Ocean Biodiversity Information System (65 records of at least14 species), and the citizen science project Mediterranean Elasmobranchs Citizen Observations (117 records per 23 species). Our updated checklist reports 60 species that account for about 70% of the Mediterranean chondrichthyan biota. The list includes 15 more species than the previous checklist and our study reports three new species for Cyprus waters, namely the blackmouth catshark Dalatias licha, the round fantail stingray Taeniurops grabatus, and the sawback angelshark Squatina aculeata. Our research highlights the need for conservation measures and more studies regarding the highly threatened blackchin guitarfish Glaucostegus cemiculus and the devil ray Mobula mobular, and stresses the importance for training a new generation of observers to strengthen the knowledge and conservation of elasmobranchs in the region.

The Case of Lionfish (Pterois miles) in the Mediterranean Sea Demonstrates Limitations in EU Legislation to Address Marine Biological Invasions - Periklis Kleitou; Jason M. Hall-Spencer; Ioannis Savva; Demetris Kletou; Margarita Hadjistylli; Ernesto Azzurro; Stelios Katsanevakis; Charalampos Antoniou; Louis Hadjioannou; Niki Chartosia; Maria Christou; Yiannis Christodoulides; et al. (Journal of Marine Science and Engineering, 2021)
The European Regulation (EU) 1143/2014 on Invasive Alien Species entered into force in 2015, with the aim to fulfill regional and international biodiversity goals in a concerted manner. To date, the Regulation listed 66 Invasive Alien Species (IAS) that are subject to legal controls. Only one of these is marine. A recent lionfish (Pterois miles) invasion has been closely monitored in the Mediterranean and a detailed risk assessment was made about the profound impacts that this invasive fish is likely to have on the fisheries and biodiversity of the region. In 2016–21, lionfish rapidly became dominant predators along Eastern Mediterranean coasts, yet the process for their inclusion on the EU IAS list has been lengthy and is ongoing. There is an urgent need to learn from this experience. Here, we recommend improvements to the Regulation 1143/2014 and the risk assessment process to protect marine ecosystems and secure the jobs of people that rely on coastal resources.

Protect the Natives to Combat the Aliens: Could Octopus vulgaris Cuvier, 1797 Be a Natural Agent for the Control of the Lionfish Invasion in the Mediterranean Sea? - Fabio Crocetta; Maria Shokouros-Oskarsson; Nikolaos Doumpas; Ioannis Giovos; Stefanos Kalogirou; Joachim Langeneck; Valentina Tanduo; Francesco Tiralongo; Riccardo Virgili; Periklis Kleitou (Journal of Marine Science and Engineering, 2021)
Biological invasions constitute a major threat to native ecosystems and to global biodiversity [...]

Feeding ecology of the highly threatened common bottlenose dolphin of the Gulf of Ambracia, Greece, through stable isotope analysis - Asunción Borrell; Morgana Vighi; Tilen Genov; Ioannis Giovos; Joan Gonzalvo (Marine Mammal Science, 2021)
The Gulf of Ambracia, in northwestern Greece, hosts a highly threatened community of about 150 common bottlenose dolphins ( Tursiops truncatus ). Until now, information on their feeding habits was derived exclusively from fish scale samples collected during surface‐feeding events targeting small schooling epipelagic fish. The aim of this study was to determine the diet of bottlenose dolphins living in the Gulf of Ambracia through the application of Bayesian isotopic mixing models. Skin biopsy samples of 16 dolphins were analyzed and no difference related to sex or age‐class was found in δ 13 C and δ 15 N values. Results suggested that the dolphin diet was mainly based on Trachurus trachurus , species belonging to the family Sparidae: Diplodus annularis , Lithognathus mormyrus , and Sepia officinalis , which represented together about 42% ± 15% of the biomass ingested, followed by species belonging to the order Clupeiformes ( Engraulis encrasicolus, Sardinella aurita, and Sardina pilchardus ) and the genus Gobius (37% ± 17%). A better understanding of the feeding habits of these dolphins sheds light on the feeding ecology of this highly threatened population by, for instance, evidencing interactions with artisanal fisheries sharing the same target species, and is key for identifying adequate management measures consistent with an ecosystem‐based approach.

Additional Records of Tripletail Lobotes surinamensis (Bloch, 1790), from the Eastern Mediterranean - Vasileios Minasidis; Nikolaos Doumpas; Periklis Kleitou; Roxani Naasan Aga Spryridopoulou; Paschalis Papadamakis; Ioannis Giovos (Thalassas: An International Journal of Marine Sciences, 2020)

Social media: a valuable tool to inform shark conservation in Greece - CHRISTOS TAKLIS; IOANNIS GIOVOS; ALEXANDROS A. KARAMANLIDIS (Mediterranean Marine Science, 2020)
Sharks in the Mediterranean Sea are facing an elevated risk of extinction; several species are considered endangered and some have been reduced to such low population numbers that they are hard to detect through conventional monitoring methods. The recent emergence of new technologies, such as social media, makes it easier to collect and transmit information that may contribute to the conservation of endangered species. From 2017 – 2019 we carried out a project in Greece that searched social media (i.e. Facebook, Twitter and YouTube) postings with the aim of collecting data on the occurrence and basic biological parameters of sharks in the country and their interactions with fisheries. We recorded 116 social media postings referring to sharks in Greece, of which, 100 were identified to the lowest taxonomic level; sixty four percent of these postings referred to threatened sharks, while the majority of them referred to species that had not been evaluated for the Greek Red Data Book. Sharks occurred throughout the country, were often involved in negative fishery interactions and were rarely reported to have been released back to the sea. Endangered sharks were often misidentified as commercially valuable species. Our study highlights the importance of social media as a valuable tool in collecting baseline information, while identifying and/or focusing on important conservation issues about sharks in Greece.

MEDLEM database, a data collection on large Elasmobranchs in the Mediterranean and Black seas - CECILIA MANCUSI; ROMANO BAINO; CATERINA FORTUNA; LUIS GIL DE SOLA; GABRIEL MOREY; MOHAMED NEJMEDDINE BRADAI; ARGYRIOS KALLIANOTIS; ALEN SOLDO; FARID HEMIDA; ADIB ALI SAAD; MARK DIMECH; PANAGIOTA PERISTERAKI; et al. (Mediterranean Marine Science, 2020)
The Mediterranean Large Elasmobranchs Monitoring (MEDLEM) database contains over 3000 records (more than 4000 individuals) of large elasmobranch species from 20 different countries around the Mediterranean and Black seas, observed from 1666 to 2017. The main species included in the archive are the devil fish (1 813 individuals), the basking shark (939 individuals), the blue shark (585 individuals) and the great white shark (337 individuals).In the last decades other species such as the shortfin mako (166 individuals), the spiny butterfly ray (138) and the thresher shark (174 individuals) were reported with an increasing frequency. This was possibly due to an increased public awareness on the conservation status of sharks, and a consequent development of new monitoring programmes. MEDLEM does not have a homogeneous reporting coverage throughout the Mediterranean and Black seas and it should be considered as a database of observed species presence. Scientific monitoring efforts in the south-eastern Mediterranean and Black seas are generally lower than in the northern sectors and the absence in our database of some species does not imply their actual absence in these regions. Some considerations are made on the frequency and spatial distribution of records, size structure of the observed individuals for selected species, general area coverage and species involved as by-catch by fishing gear.

Updating the occurrences of Pterois miles in the Mediterranean Sea, with considerations on thermal boundaries and future range expansion - CHARALAMPOS DIMITRIADIS; MARIKA GALANIDI; ARGYRO ZENETOS; MARIA CORSINI-FOKA; IOANNIS GIOVOS; PARASKEVI K. KARACHLE; IVONI FOURNARI – KONSTANTINIDOY; ELENI KYTINOU; YIANNIS ISSARIS; ERNESTO AZZURRO; LUCA CASTRIOTA; MANUELA FALAUTANO; et al. (Mediterranean Marine Science, 2020)
Here we present an update of the Mediterranean distribution of the lionfish Pterois miles, based on a comprehensive list of geo-referenced occurrences up to October 2019. New data were provided by multiple reporting tools and citizen science initiatives. Our findings suggest that well established populations of P. miles exist in the Levantine Sea, in the southern and central Aegean Sea, as well as in the Greek Ionian Sea, whilst so far, only a few individuals were reported from Tunisia and southern Sicily (Italy). We also argue about the future expansion of this invasive species in the Mediterranean region and about the role of climate change by projecting the limits of winter isotherms under different climate change scenarios. Under the assumption that the mean winter sea surface temperature is the main limiting factor of the range expansion of the species (i.e. 15.3oC winter isotherm), P. miles could substantially expand in the Mediterranean Sea, except the coolest northernmost regions, under future climatic scenarios. These results were discussed in comparison to published outcomes of species distribution modelling.

Filling the Gap of Data-Limited Fish Species in the Eastern Mediterranean Sea: A Contribution by Citizen Science - Roxani Naasan Aga Spyridopoulou; Joachim Langeneck; Dimitris Bouziotis; Ioannis Giovos; Periklis Kleitou; Stefanos Kalogirou (Journal of Marine Science and Engineering, 2020)
The biodiversity of the Mediterranean Sea is rapidly changing due to anthropogenic activity and the recent increase of seawater temperature. Citizen science is escalating as an important contributor in the inventory of rare and data-limited species. In this study, we present several records of five data-limited native fish species from the eastern Mediterranean Sea: Alectis alexandrina (Geoffroy Saint-Hilaire, 1817), Ranzania laevis (Pennant, 1776), Dalatias licha (Bonnaterre, 1788), Lophotus lacepede (Giorna, 1809), and Sudis hyalina (Rafinesque, 1810). All of the records were collected by a participatory process involving fishers and validated by associated taxonomic experts of the citizen science programme “Is it Alien to you? Share it!!!”. This study fills an important gap for the distribution of the reported species and signifies the important role of citizen participation as a tool for extending marine biodiversity knowledge and fisheries management in an area with several gaps of knowledge on targeted and non-targeted species.

The Indo-Pacific Sergeant Abudefduf vaigiensis (Quoy & Gaimard, 1825) (Perciformes: Pomacentridae) in Libya, South-Central Mediterranean Sea - David Osca; Valentina Tanduo; Francesco Tiralongo; Ioannis Giovos; Sara A. A. Almabruk; Fabio Crocetta; Jamila Rizgalla (Journal of Marine Science and Engineering, 2019)
The Indo-Pacific Sergeant Abudefduf vaigiensis (Quoy & Gaimard, 1825) (Chordata: Pisces: Actinopterygii: Perciformes: Pomacentridae) is first recorded in the south-central Mediterranean Sea (Libya), based on the external morphology and the barcoding of a fragment of the cytochrome c oxidase subunit I gene. Present sightings from field surveys and social media include juveniles, sub-adults, and a single adult specimen, suggesting that the species is now established in Libyan waters. No certainties occur regarding timing and possible pathway of arrival of this species in the area, and it may have simply gone undetected for years. The joint effort of field studies and citizen science projects in collaboration with international organizations continues shedding light on bioinvasions in Libya, with valuable outcomes for the Mediterranean marine biology as a whole.

Citizen-science for monitoring marine invasions and stimulating public engagement: a case project from the eastern Mediterranean - Ioannis Giovos; Periklis Kleitou; Dimitris Poursanidis; Ioannis Batjakas; Giacomo Bernardi; Fabio Crocetta; Nikolaos Doumpas; Stefanos Kalogirou; Thodoros E. Kampouris; Ioannis Keramidas; Joachim Langeneck; Mary Maximiadi; et al. (Biological Invasions, 2019)

New Mediterranean Biodiversity Records (November 2018) - MEHMET BAKİ YOKEŞ; VASILIS ANDREOU; RIGERS BAKIU; SARA BONANOMI; JUDITH CAMPS; GEORGE CHRISTIDIS; FABIO CROCETTA; IOANNIS GIOVOS; ANDREA GORI; TEA JURETIĆ; SELAHATTİN ÜNSAL KARHAN; STELIOS KATSANEVAKIS; et al. (Mediterranean Marine Science, 2018)

Identifying recreational fisheries in the Mediterranean Sea through social media - Ioannis Giovos; Ioannis Keramidas; Charalampos Antoniou; Alan Deidun; Toni Font; Periklis Kleitou; Josep Lloret; Sanja Matić‐Skoko; Alicia Said; Francesco Tiralongo; Dimitrios K. Moutopoulos (Fisheries Management and Ecology, 2018)
The impact of recreational fishing on fish stocks remains largely unknown, as this is inherently difficult to monitor, especially in areas such as the Mediterranean Sea where many species are targeted using a variety of fishing gears and techniques. This study attempts to complement existing data sets and construct the profile of recreational fisheries in the EU ‐Mediterranean countries using videos publicly available on social media. A total of 1526 video records were selected, featuring the capture of 7799 fish specimens. The results show recreational fishing is multispecies in nature (26 species contributed to >80% % of the most numerically important species caught) and exhibits a spatially homogeneous pattern, with differences in species composition being mostly dependent on the fishing technique used rather than on the country. Such findings fill an important knowledge gap on recreational fishing activities, and the methodology provides an innovative approach to gather statistics on data‐poor thematic areas that can potentially complement other data sets, such as the EU Data Collection Multi‐Annual Programme.

Biological Invasions in Conservation Planning: A Global Systematic Review - Vesna Mačić; Paolo G. Albano; Vasiliki Almpanidou; Joachim Claudet; Xavier Corrales; Franz Essl; Athanasios Evagelopoulos; Ioannis Giovos; Carlos Jimenez; Salit Kark; Olivera Marković; Antonios D. Mazaris; et al. (Frontiers in Marine Science, 2018)